Fungsi Kepemimpinan Kepala Madrasah Tsanawiyah Negeri 2 Kota Palu - Ridwan Ridwan; Ahmad Fiqri R (Sekolah Tinggi Ilmu Administrasi (STIA) Pembangunan Palu, 2021)
This study aims to determine how the Leadership Function of the Head of Madrasah Tsanawiyah Negeri 2 Palu City. This type of research is descriptive, while the basis of this research is qualitative, where in this study the researcher tries to reveal real and objective facts about the Leadership Function of the Madrasah Head at Madrasah Tsanawiyah Negeri 2 Palu. This study uses the theory of Mulyasa (2007), namely as educators, managers, administrators, supervisors, leaders, innovators, and as motivators. The results showed that the leadership function of the head of the Madrasah Tsanawiyah Negeri 2 Palu City in carrying out its function as a leader had gone well, where the Head of the Madrasah in carrying out his duties and responsibilities as a leader to direct teachers and other education personnel, as well as carry out tasks jointly. together in improving the quality of education and progress of Madrasah Tsanawiyah Negeri 2 Palu